Assédio moral: uma analise da teoria do abuso de direito aplicada ao poder do empregador - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2007)
The subject of the present dissertation focus on the characterization of the moral harassment phenomenon in the employment relationship and its legal treatment. The analysis begins on the ways power is reveled in the working environment and the legal subordination of the employee, especially focusing the employer directive power condition. Next, the production restructuring implications is investigated in search of understanding the way new production patterns interacts in the construction of subjective working ( employee role ) and makes it possible for the employer to abuse of his directive power in a way which may be characterized as moral harassment. The problems involving the abuse of rights theory application and the treatment given to abusive practices in the working environment is also analyzed in search of a legal strategy to face moral harassment. At last, the regularizing law proposals of conditions for the moral harassment punishment in the working environment and the moral harassment as it is seen by Courts is examined.
Keywords: assédio moral; poder; subordinação; abuso de direito; moral harassment; power; subordination; abuse of rights; CNPQ::CIENCIAS SOCIAIS APLICADAS